2023
DOI: 10.3390/diseases11010014
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Social Patterns of the Mean Values of Inflammatory Markers in U.S. Adults: A 2009–2016 NHANES Analysis

Abstract: Several studies have reported on the negative implications of elevated neutrophil-to-lymphocyte ratio (NLR) and elevated platelet-to-lymphocyte ratio (PLR) levels associated with outcomes in many surgical and medical conditions, including cancer. In order to use the inflammatory markers NLR and PLR as prognostic factors in disease, a normal value in disease-free individuals must be identified first. This study aims (1) to establish mean values of various inflammatory markers using a healthy and nationally repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
3
2
Order By: Relevance
“…This outcome is consistent with a study that Meng et al published, which indicated that the NLR, but not the PLR, of DED patients was reportedly higher than that of healthy subjects 25 . Also, NLR and PLR value are dependent on population characteristics such as race 38,57 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This outcome is consistent with a study that Meng et al published, which indicated that the NLR, but not the PLR, of DED patients was reportedly higher than that of healthy subjects 25 . Also, NLR and PLR value are dependent on population characteristics such as race 38,57 …”
Section: Discussionsupporting
confidence: 91%
“…25 Also, NLR and PLR value are dependent on population characteristics such as race. 38,57 The DM2-DED had increased levels of SII as well as HbA1c. In addition, SII values were found to be considerably higher in patients with DM2-DED and DM2 than healthy and DED only.…”
Section: Discussionmentioning
confidence: 99%
“…For example, men often have a higher NLR and monocyte count than females. 16,17 In our study, the percentage of men was 63.3%, surpassing the figures of Silva-Vaz, Biyik, and Yildiz, where the male percentages were 31.0%, 45.5% and 52.8%, respectively. Furthermore, diabetic patients typically exhibit a higher NLR than the general population.…”
Section: Discussioncontrasting
confidence: 82%
“…There are many factors that can affect the NLR and monocyte beyond AP. For example, men often have a higher NLR and monocyte count than females 16,17 . In our study, the percentage of men was 63.3%, surpassing the figures of Silva‐Vaz, Biyik, and Yildiz, where the male percentages were 31.0%, 45.5% and 52.8%, respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…Sensitivity analysis was conducted by excluding the participants with incomplete data in covariates. Taking the biochemical markers between human races into consideration ( 37 ), a subgroup analyses between races were performed using a stratified logistic regression model and a interaction test for effect modification for different races were followed by the likelihood-ratio test. Data analysis was performed with the statistical software packages R 2 and EmpowerStats ( http://www.empowerstats.com , X&Y Solutions, Inc., Boston, MA).…”
Section: Methodsmentioning
confidence: 99%